2018
DOI: 10.3138/cmlr.3889
|View full text |Cite
|
Sign up to set email alerts
|

Enseigner en immersion française au Canada : synthèse des connaissances sur les défis et leurs implications pour la formation des enseignants

Abstract: Cet article présente les résultats d’une synthèse des connaissances visant à identifier comment la thématique de la formation initiale et continue concernant les défis liés à l’enseignement en milieu immersif francophone au Canada a été traitée dans les études et travaux théoriques ces dix dernières années. L’analyse des travaux répertoriés révèle des défis importants quant au développement d’une pédagogie adaptée à un contexte éducatif de plus en plus linguistiquement et culturellement hétérogène et qui doit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Opening a space for other languages in mainstream classrooms through translated or bilingual texts can foster self-refl ection among students' and their peers' use of home languages, ultimately leading to a greater understanding of their own multilingualism as a resource for academic learning (Po s, 2010). It is hoped that this brief article contributes to FSL teacher candidates' continued unlearning of monoglossic language ideologies in support of heteroglossic language practices (Flores & Bale, 2016), as well as corresponding approaches to assessment (Jared, 2008) in bilingual classrooms, and possibly inspires much-needed research (Cammarata, Cavanagh, Blain, & Sabatier, 2018) that a ends to the experiences of FSL teacher candidates.…”
Section: Final Thoughtsmentioning
confidence: 94%
“…Opening a space for other languages in mainstream classrooms through translated or bilingual texts can foster self-refl ection among students' and their peers' use of home languages, ultimately leading to a greater understanding of their own multilingualism as a resource for academic learning (Po s, 2010). It is hoped that this brief article contributes to FSL teacher candidates' continued unlearning of monoglossic language ideologies in support of heteroglossic language practices (Flores & Bale, 2016), as well as corresponding approaches to assessment (Jared, 2008) in bilingual classrooms, and possibly inspires much-needed research (Cammarata, Cavanagh, Blain, & Sabatier, 2018) that a ends to the experiences of FSL teacher candidates.…”
Section: Final Thoughtsmentioning
confidence: 94%
“…In Canada, excluding the province of Québec, research and standardised testing over the past two decades have revealed a gap in writing achievement between students from English‐language public schools and those from French‐language public schools (Conseil des ministres de l'éducation, 2004; Programme pancanadien d'évaluation, 2019). This gap has been explained by numerous factors, including the difficult relationship that French‐speaking students have with the French language and culture (Blain et al, 2018), academic‐based challenges (Cavanagh et al, 2016), systemic inequities (Dalley and Roy, 2008; Gélinas‐Proulx and Villella, 2022), and the lack of appropriate resources and training in the explicit teaching of writing strategies (Gratton et al, 2014). Given the fact that ‘writing activities are the key components of critical thinking and efficient learning’ (İncirci and Şükrü Parmaksiz, 2016, p. 1263), if teacher education programmes do not attend to writing instruction, then the disparity in writing competency between Francophones (the minority) and Anglophones (the majority) will keep growing.…”
Section: Contextmentioning
confidence: 99%
“…In an article that synthesizes a retrospective view of immersion research during the last ten years, Cammarata, Cavanagh, Blain, and Sabatier (2018) highlight these challenges in relation to both the development of a pedagogy adapted to an educational context that is increasingly diverse, linguistically and culturally, and to teacher preparation and development.…”
Section: Literature Reviewmentioning
confidence: 99%